2022
DOI: 10.5498/wjp.v12.i8.1088
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19 and emotional dysfunction problems: Intrusive, avoidance and hyperarousal stress as key mediators

Abstract: BACKGROUND There is mounting empirical evidence of the detrimental effects of the coronavirus disease 2019 (COVID-19) outbreak on mental health. Previous research has underscored the effects of similar destabilizing situations such as war, natural disasters or other pandemics on acute stress levels which have been shown to exacerbate current and future psychopathological symptoms. AIM To explore the role of acute stress responses (intrusive, avoidance and hyperarousal) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Moreover, SAD individuals scored higher (d = 1.02, p < 0.001) for fears associated with social distancing (e.g., "I am afraid I will lose my friends because of a bad illness or virus") and higher (d = 1.19, p < 0.01) for how much these fears impacted the participant's life (e.g., "being afraid of an illness or virus has caused me to feel experience strong emotions"). Consistent with these results, Falco et al [52], using a DSM-5-based self-report questionnaire, conducted a path mediation and found intrusive stress (e.g., repeated thoughts about the stressful event) to be related to social anxiety (β = 0.21, 99% CI > 0.0). Additionally, hyperarousal stress, such as anger and irritability, difficulty concentrating and hypervigilance, was related to social anxiety (β = 0.17, 99% CI > 0.0).…”
Section: The Covid-19 Pandemic's Effects On Individuals With Sadmentioning
confidence: 69%
See 2 more Smart Citations
“…Moreover, SAD individuals scored higher (d = 1.02, p < 0.001) for fears associated with social distancing (e.g., "I am afraid I will lose my friends because of a bad illness or virus") and higher (d = 1.19, p < 0.01) for how much these fears impacted the participant's life (e.g., "being afraid of an illness or virus has caused me to feel experience strong emotions"). Consistent with these results, Falco et al [52], using a DSM-5-based self-report questionnaire, conducted a path mediation and found intrusive stress (e.g., repeated thoughts about the stressful event) to be related to social anxiety (β = 0.21, 99% CI > 0.0). Additionally, hyperarousal stress, such as anger and irritability, difficulty concentrating and hypervigilance, was related to social anxiety (β = 0.17, 99% CI > 0.0).…”
Section: The Covid-19 Pandemic's Effects On Individuals With Sadmentioning
confidence: 69%
“…Additionally, Blasco-Belled et al [46] found that social anxiety correlated significantly with a COVID-19 threat item. In Falco et al [52], scores on fear of COVID-19 were large for a high social anxiety group compared to a low social anxiety group, reaching an almost moderate effect size (Hedge's g = 0.47, p = 0.003). In Moran [68], fear of COVID-19 had a positive but non-significant correlation with social anxiety (r = 0.12, p = 0.52), although this was possibly due to the small sample size (n = 32).…”
Section: Contracting Covid-19mentioning
confidence: 85%
See 1 more Smart Citation
“…Additionally, [39] found a signi cant correlation between intrusive pandemic-related stress, conceptualized as repetitive negative thoughts about the COVID-19 pandemic, and social anxiety. Speci cally, the pandemic-related stress was assessed as PTS symptoms, including avoidance of awareness, intrusive thinking, and hyperarousal, with the last two resulting positively related to social anxiety [39]. The pandemic might have caused indeed life-threating events (e.g.…”
Section: Social Anxiety and Emotional Impact Of Events During Covid-1...mentioning
confidence: 94%